Surgical treatment of kaposiform hemangioendothelioma in the pelvic cavity, bladder and ureter - Li Xiao; Changxian Dong; Song Zuo; Yanlin Wang (Elsevier, 2018)
Kasabach-Merritt phenomenon (KMP) is a rare potentially life-threatening consumptive coagulopathy characterized by thrombocytopenia and hypofibrinogenemia occurring associated with the vascular tumors kaposiform hemangioendothelioma (KHE) and tufted angioma (TA). KHE in the specific sites will also cause some non-hemorrhagic complications. We report a two-month old female infant with KHE in her pelvic cavity, bladder and ureter who responded well to surgical excision. Keywords: Kaposiform hemangioendothelioma, Kasabach-Merritt phenomenon, Pelviccavity, Bladder, Ureter, Surgical excision, Thrombocytopenia, Coagulopathy, Therapy